Representing the Cultural Dimension of Meaning in Learner’s Dictionaries — From the Perspective of Chinese EFL Learners in L2 Reception - Xue, Mei (Lexikos, 2017)
Meaning in dictionaries ranks as the most frequent data type consulted by language learners. An extensive range of devices have been developed to represent the meaning of lexical items in learner’s dictionaries. Starting from interpreting foreign language learners’ lexicographic needs in specific user situations, this paper aims to examine the implications of customizing definitions from the cultural perspective with specific reference to Chinese learners of English. The purpose of this paper is three-fold: i) to understand the status quo of the lexicographic practice of English learner’s dictionaries in terms of representing the cultural dimension of a lexical item; ii) to interpret the impacts of foreign language learners’ language and cultural background on their lexicographic needs in terms of cultural aspects in L2 reception; iii) to address the identified problems with present lexicographic practices through model articles. It is expected that the findings in this paper can shed some light on interpreting other ethnic groups of learners’ lexicographic needs in different situations and contribute to improving the services of learner’s dictionaries in the future as well.